Comparison of outcomes between minimally invasive transforaminal lumbar interbody fusion and traditional posterior lumbar intervertebral fusion in obese patients with lumbar disk prolapse - Wang YP; An JL; Sun YP; Ding WY; Shen Y; Zhang W (Dove Medical Press, 2017)
Ya-Peng Wang,* Ji-Long An,* Ya-Peng Sun,* Wen-Yuan Ding, Yong Shen, Wei Zhang Department of Spinal Surgery, The Third Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China *These authors contributed equally to this work Objective: The aim of this study was to compare the curative effect between minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) and the posterior lumbar interbody fusion (PLIF) in obese patients with lumbar disk prolapse.Patients and methods: In this study, 72 patients who underwent lumbar disk prolapse therapy in the Third Hospital of Hebei Medical University between March 2011 and 2015 were retrospectively analyzed and were divided into two groups, MIS-TLIF group (n=35) and PLIF group (n=37), according to different surgical procedures. Several clinical parameters were compared between these two groups.Results: Compared with PLIF, MIS-TLIF was associated with longer operative time, less blood loss, less postoperative drainage and shorter postoperative time in bed; moreover, patients in the MIS-TLIF group had lower levels of serum creatine kinase on 1, 3 and 5 postoperative days. At the 3- and 6-month follow-up, Visual Analog Scale (VAS) scores of low back pain of patients in the MIS-TLIF group were significantly reduced and Japanese Orthopaedic Association (JOA) scores were increased, whereas the Oswestry Disability Index (ODI) showed no significant difference between the two groups.Conclusion: Obese patients can achieve good efficacy with MIS-TLIF or PLIF treatment, but MIS-TLIF surgery showed longer operative time, fewer traumas and bleeding volume, less incidence of short-term pain, low complication rate and faster postoperative recovery. Keywords: lumbar degenerative diseases, obesity, minimally invasive, spinal fusion, surgical complications